The marketing of regions in the context of regional development strategies - Mielke, Bernd (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
In the face of increasing competition between regions, the mobilisation of regional potentials is gaining importance. The concept of the marketing of regions can complement other development initiatives at the regional level. For this to be achieved, the marketing initiatives have to find their specific role within the development process. They have both to delimit themselves from existing institutions and initiatives and to co-operate with these actors. In particular, co-operation between the spatial planning authorities and the marketing initiatives seems to be desirable.